Konsep Modernisasi/Globalisasi Terhadap Pengembangan Organisasi Publik - Aditya Saputra (JURNAL ILMIAH ILMU ADMINISTRASI, 2021)
traditional society towards a more advanced society. This is a shift in people's attitudes and mentality to suit today's life demands. To develop a public organization is not an easy matter. From time to time the challenges faced will always change over time, one of which is the occurrence of globalization. Globalization is a new challenge for every Public Organization in developing its organization. Because with the mixing of global cultures that come, making public organizations become more developed, so they can compete with other organizations.